Effect of oat restricted grazing on milk production - Rodrigues, Armando de Andrade; Godoy, Rodolfo (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this research was to evaluate the effect of oat (Avena sp.) restricted grazing on milk production. Twelve crossbred dairy cows (holstein-zebu) were used in a complete randomized block design. The cows were allocated to two treatments: A. restricted grazing on oat (3 hours day-1) plus 10 kg of corn silage; B. corn silage ad libitum as the only forage. All animals received 5.0 kg of concentrate head-1 day-1 with 19% crude protein (CP) and 75% total digestible nutrientes (TDN). There was no statistical difference (P > 0.05) between A and B treatments in milk production (14.6 vs. 13.3 kg cow-1 day-1). Difference was found (P < 0.05) in fat content (3.4 vs 3.8%), but this did not affect (P < 0.05) 4% milk corrected production. Difference was found also in weight gain (P < 0.08). The cows that had access to restricted grazing on oat gained 0.53 kg day-1 and the cows that received corn silage as the only forage gained 0.25 kg day-1. It was concluded that restricted grazing on São Carlos oat cultivar allow high milk production with crossbred cows.